2002
DOI: 10.1007/s00412-001-0177-x
|View full text |Cite
|
Sign up to set email alerts
|

P element-mediated duplications of genomic regions in Drosophila melanogaster

Abstract: Previously we have described highly unstable yellow mutations induced by chimeric elements that consist of genomic sequences originating from different regions of the X chromosome flanked by identical copies of an internally deleted 1.2 kb P element. To study further the origin and the mechanism of formation of chimeric mobile elements, we analyzed complex y-sc mutations, induced by inversions between P elements located in the neighboring yellow and scute loci. The breakpoints of the inversions are flanked by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Hereafter, the Pfry 1 D2-3g99B construction is referred to as D2-3. The highly unstable mutations in the yellow locus used in this work have been described (Georgiev et al 1997;Golovnin et al 2002). All other mutant alleles and chromosomes as well as balancer chromosomes have been described in Lindsley and Zimm (1992).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Hereafter, the Pfry 1 D2-3g99B construction is referred to as D2-3. The highly unstable mutations in the yellow locus used in this work have been described (Georgiev et al 1997;Golovnin et al 2002). All other mutant alleles and chromosomes as well as balancer chromosomes have been described in Lindsley and Zimm (1992).…”
mentioning
confidence: 92%
“…The mutations were large in number for all the genes, with a full spectrum of phenotypes. Some highly unstable mutations in the yellow gene were molecularly characterized (Georgiev et al 1997;Golovnin et al 2002). These mutations were generated by insertion of a chimeric element at ÿ69 bp relative to the yellow transcription start site.…”
mentioning
confidence: 99%
“…Golovnin et al (2002) found numerous insertions and inversions in a region containing three P elements. Comparable events have also been analysed in other eukaryotes, including Ac in maize (Zhang and Peterson, 1999) and a Tc1-mariner element, impala, in the fungus Fusarium (Hua- Van et al, 2002).…”
Section: Discussionmentioning
confidence: 99%